Urgensi Regulasi Khusus untuk Perlindungan Data Genomik di Indonesia: Studi Perbandingan dengan GDPR dan Australian Privacy Act. - Dewi Asri Puananndini; Aldi Satya Putranto; Mustafid Mustafid; Indah Thalita (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to analyze the urgency of specific regulations for genomic data protection in Indonesia using a normative juridical approach and a comparative legal method with the European Union's General Data Protection Regulation (GDPR) and the Australian Privacy Act. Genomic data has unique characteristics that distinguish it from other personal data, requiring stricter legal protection. The analysis examines Indonesia’s Personal Data Protection Law (Law No. 27 of 2022) to identify regulatory weaknesses in ownership rights, informed consent mechanisms, data security, and cross-border data transfers. The findings reveal that Indonesia lacks explicit provisions recognizing genomic data as a special category requiring higher protection standards. Referring to best practices from the GDPR and the Australian Privacy Act, this study recommends establishing specific regulations covering data ownership protection, strengthening consent mechanisms, and enhancing oversight of genomic data security and transfers. Implementing stricter regulations is expected to safeguard individual privacy while supporting research and innovation in healthcare and biotechnology.